Relationship between serum magnesium values, lipids and anthropometric risk factors - Randell, Edward W.; Mathews, Maria; Gadag, Veeresh; Zhang, Hongwei; Sun, Guang (Atherosclerosis, 2008)
Serum magnesium (SMg) has been reported to negatively correlate with an atherogenic lipid profile in individuals with diabetes mellitus (DM) and metabolic syndrome. This study examines whether the relationships between SMg levels and biochemical and anthropometric risk factors for these conditions are also present in the general adult population. Biochemical parameters and anthropometric variables were assessed in 1318 healthy adult subjects recruited from the Newfoundland population. SMg positively correlated with age, and serum phosphate, calcium, albumin, total cholesterol, HDL-cholesterol, LDL-cholesterol and triglyceride levels. SMg negatively correlated with HOMA-β and percent body fat measured by DEXA. On sub-grouping subjects according to sex, menopausal status or after excluding subjects with DM, only a significant correlation of SMg with albumin, calcium, phosphate, and total cholesterol was common to all. Stepwise linear regression analysis revealed albumin, phosphate, age, total cholesterol, glucose, and body mass index as independent predictors of SMg levels. These results indicate that SMg levels positively correlate with total cholesterol and possibly all lipoproteins in a large adult study population which suggests that variation of SMg with serum lipid levels may be different in healthy individuals compared with those with DM. We speculate on a possible binding interaction.